Impact of Non-Alcoholic Fatty Liver Disease on Metabolic Comorbidities in Type 2 Diabetes Mellitus - Labenz, Christian; Kostev, Karel; Alqahtani, Saleh A.; Galle, Peter R.; Schattenberg, Jörn M. (Experimental and Clinical Endocrinology & Diabetes, 2021)
Objective Type 2 Diabetes (T2D) is a major risk factor for the development and progression of non-alcoholic fatty liver disease (NAFLD). The published prevelance in epidemiological studies in this high risk population exceeds 70%. The aim of this analysis was to investigate the impact of NAFLD on T2D patients in Germany.Methods Using the Disease Analyzer Database (IQVIA), T2D patients with NAFLD diagnosed in Germany were matched to a cohort without NAFLD controlling for age, sex, physician, index year and metabolic comorbidities and assessed for their risk of developing myocardial infarction, stroke, peripheral arterial disease (PAD) or chronic kidney disease, as well as the type of T2D treatment on NAFLD.Results 2633 T2D patients with NAFLD were matched to 2633 T2D patients without liver disease. The ICD coded prevalence of NAFLD in patients with T2D in primary care in Germany was 7.8%. On regression analysis of patients with T2D , the presence of NAFLD was associated with a higher risk of renal failure during follow-up (HR 1.17, 95% CI 1.02–1.34, p=0.027). No association with the development of myocardial infarction, stroke, PAD or initiation of insulin therapy was observed. NAFLD patients were more frequently treated with DDP-4 inhibitors (+/-metformin) and less frequently with insulin within the first year of T2D diagnosis. The metabolic control (HbA1c range 6.5–7.5%) during follow-up did not differ between both groups.Conclusion The coded prevalence of NAFLD in T2D patients is low, which is in contrast to published series. Enhancing disease awareness of NAFLD and screening recommendations in high risk populations will be beneficial for the active management of these patients.
Keywords: liver disease; cirrhosis; metabolic comorbidities; disease burden; hyperglycemia